PERSEPSI STAKEHOLDTuna revitalization program undertaken by PPN Ternate indicate a change in the management of fish resources and the expansion of seed not only focus on ER USAHA PENANGKAPAN TUNA DI PELABUHAN PERIKANAN NUSANTARA (PPN) TERNATE MALUKU UTARA - Titien Sofiati; Domu Simbolon; Tri Wiji Nurani; Eko Sri Wiyono (Sosiohumaniora, 2014)
Tuna revitalization program undertaken by PPN Ternate indicate a change in the management offish resources and the expansion of seed not only focus on skipjack but also on tuna resources. Perceptions ofstakeholders have an important role and is affecting their engagement towards fisheries management system thatwill be applied. The study was conducted during the two months of January and February 2013 with interviewsand surveys. Perception analysis be descriptive of the factors that influence the tuna fishing effort in PPN Ternate,deskriminan multiple testing using the equation to obtain a perceptual map (perceptual map). Public perceptionof tuna landed in PPN Ternate can provide a proof of the success of the tuna revitalization program undertakenby PPN Ternate. Based on the results of research conducted can be concluded that the tuna fishing business isgrowing and should continue to be developed.Keywords: Perception, PPN Ternate, stakeholder, tuna